FUNDAMENTALS OF MODERN APPROACH TO TEACHING UZBEK NATIONAL MUSICAL ART (American Journal of Interdisciplinary Research and Development, 2024)
This scientific article analyzes the foundations of modern approaches to the teaching of Uzbek national musical art. The article examines the importance of active teaching methods, modern technologies and individual approaches in the educational process. Information is provided about the activities carried out in order to introduce new pedagogical approaches to teaching the rich heritage of Uzbek national musical art, to develop student creativity and preserve cultural heritage. The article contains important recommendations to make the process of teaching Uzbek national music more effective and interesting.